Producing carbon nanotubes from thermochemical conversion of waste plastics using Ni/ceramic based catalyst. (31st December 2018) - Liu, Xiaotong; Shen, Boxiong; Wu, Zhentao; Parlett, Christopher M.A.; Han, Zhenan; George, Adwek; Yuan, Peng; Patel, Dipesh; Wu, Chunfei
Highlights: Ni/ceramic catalyst was used to successfully produce CNTs from waste plastics. CNTs with uniform diameter distribution was obtained. 1.0/ceramic catalyst was found to be the best for CNTs production. Catalytic temperature of 700 °C was found to be optimal for CNTs production. Abstract: As the amount of waste plastic increases, thermo-chemical conversion of plastics provides an economic flexible and environmental friendly method to manage recycled plastics, and generate valuable materials, such as carbon nanotubes (CNTs). The choice of catalysts and reaction parameters are critical to improving the quantity and quality of CNTs production. In this study, a ceramic membrane catalyst (Ni/Al2 O3 ) was studied to control the CNTs growth, with reaction parameters, including catalytic temperature and Ni content investigated. A fixed two-stage reactor was used for thermal pyrolysis of plastic waste, with the resulting CNTs characterized by various techniques including scanning electronic microscopy (SEM), transmitted electronic microscopy (TEM), temperature programmed oxidation (TPO), and X-ray diffraction (XRD). It is observed that different loadings of Ni resulted in the formation of metal particles with various sizes, which in turn governs CNTs production with varying degrees of quantity and quality, with an optimal catalytic temperature at 700 °C.